The Effect of Various Concentrations of Both Lime Juice and Synthetic Citric Acid Solutions to Protect Capsicum frutescens L. against Yellow Leaf Curl Disease - Rejo Wagiman; Yohanes Hendro Agus; Bistok Hasiholan Simanjuntak (The University of Lampung, 2023)
The yellow leaf curl (YLC) disease is one of plant disease generally found in chili pepper. The aim of the research was to know various concentrations of lime juice and synthetic citric acids to protect chili pepper (Capsicum frutescens L.) against YLC disease. The research used a randomized completely block design using seven treatments and three replications. The treatments tested were spraying lime juice of 0.1%, 0.2%, and 0.3% volume per volume (v/v); citric acid solution of 0.1%, 0.2%, and 0.3 % weight per volume (w/v). Control was used water only. The data result were analyzed using the honestly significant different test at the 95% confidence level. The treatment of both lime juice and citric acid solutions 0.2% and 0.3% could decreased whitefly population on chili pepper compared with control. The lime juice and citric acid solutions 0.3% was able to reduce the incidence and intensity of YLC disease. Lime juice and citric acid solution of 0.2% and 0.3% increased fruit numbers and fruit weights compared with control. The lower whitefly population decreased disease incidence of YLC (with regression Y = 5.7505x – 48.029). Intensity of YLC disease decreased fruit numbers and fruit weight (correlation value of -0.949 and -0.912). Keywords: Citric acid, Chili pepper, Gemini virus diseases, Whitefly.